DIRECTIVES IN ENGLISH - F.X. Nadar (Humaniora, 1994)
English has many ways of expressing directives. This paper attempts to classify the examples of directives based on their linguistic forms, which then will be given some comments. These comments, despite being subjective, are based on observation and inquiries to native speakers of English. Finally, this paper discusses other possible ways which can be used to classify the directives and the implications for learners and teachers of English to speakers of other languages. Austin (quoted by Coulthard, 1985) makes the distinction between locutionary and illocutionary acts, and he says further that "the interpretation of the locutionary act concerns with meaning, the interpretation of the illocutionary act with force." Searle (cited by Coulthard, 1985 ) proposes five microclasses of illocutionary act: representatives, directives, commissives, expressives and declarations. Directives (Coulthard, 1985:24) may be defined as all attempts by the speaker to get the hearer to do something- in this class the speaker is wanting to achieve a future situation in which the world will match his words and thus this class includes no (simply 'order' and 'request' but, more subtly, "invite", 'dare' and 'challenge'.